Feasibility and Acceptability of Medical Abortion at BPKIHS - Agrawal, Ajay; Regmi, Mohan C; Uprety, Dhruba Kumar; Pokhrel, Hanoon; Rijal, Pappu (Health Renaissance, 2011)
Objective: To test the feasibility and acceptability of a simplified mifepristone-misoprostol regimen for early abortion at BPKIHS. Methods: Pregnant women (n=100) with amenorrhea of 56 days or less seeking termination of pregnancy received 200mg of oral mifepristone followed 48hours later by 400 μg of oral misoprostol, administered either at home or at the clinic. Prospective data were collected to determine the women.s experience, abortion outcome, and the operational requirement for providing the method. Result: Most (91%) of the 88 women with known outcomes had successful medical abortions. Given the option, most (95.4%) women elected to administer the misoprostol at home. Conclusion: A simplified medical abortion protocol, including home administration of misoprostol, is highly safe, effective acceptable and feasible in our setting. Keywords: medical abortion; mifepristone; misoprostol DOI: 10.3126/hren.v8i3.4205 Health Renaissance, September-December 2010; Vol 8 (No.3);142-146